Implementation and Planning of Human Resource Management in Islamic Banking Institutions - Rohprihati (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Management is an important point for a company. Planning is needed in financial institutions, including Islamic banking. It aims to coordinate the workforce effectively. For the formation of quality workforce management so that it becomes a hope that can be the foundation of Islamic banking companies in Indonesia. HR management is planning, organizing, directing, and controlling. The existence of development, payroll, maintenance, and decay are the goals of individuals and society. The challenge in implementing HR management is the workforce who does not have a sharia financial background. The rapid development of Islamic financial institutions has resulted in great opportunities for the community in muamalah activities. Islamic financial institutions in Indonesia adhere to the policies contained in the law. This study used qualitative research methods that aimed to determine the function and role of human resource management in Islamic banking institutions. The results of this study concluded that Islamic law is the basis for implementing human resource development strategies. The development of the performance and quality of the workforce carried out by Islamic banks by providing regular training to all workers aims to improve the quality of the workforce. The lack of education in Islamic banking introduces an understanding based on Islamic law. The workforce in Islamic banking institutions aims to regulate and improve the system so that it can run effectively.